Storytelling with virtual reality in 360-degrees: a new screen grammar - Dooley, Kath (Taylor & Francis, 2017)
With reference to three recently produced Australian case studies, this article explores approaches to the conceptualization and writing of short narratives for the emerging medium of cinematic 360-degree virtual reality. Storytelling for this format involves a user-focused engagement with time and place. Whereas the viewer of classical narrative media, such as film or television, is for the most part passive, the VR viewer is ‘present’ as an active agent who engages with the unfolding narrative as either witness or participant. These factors present a number of challenges and opportunities for the creator of narrative VR, when considering viewer immersion and/or interaction in the 360-degree environment. The article presents a review of literature that interrogates the specifics of writing for VR, with a specific focus on 360-degree, immersive projects. By interrogating the form of three recently produced works, the author highlights emerging approaches to narrative structure, audience acclimation and the directing of viewer attention. While some commonalities can be observed across these case studies, the article concludes that to date, there is no one approach and no fully established screen grammar associated with a 360-degree VR narrative.